2009
DOI: 10.1038/sj.bjc.6605152
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of S-1 and cisplatin with concurrent radiotherapy for locally advanced non-small-cell lung cancer

Abstract: BACKGROUND: To assess the efficacy and safety of S-1 and cisplatin with concurrent thoracic radiation for unresectable stage III non-small-cell lung cancer (NSCLC). METHODS: Eligible patients were 20 -74 years old and had histologically or cytologically confirmed NSCLC, a performance status of 0 -1, and no prior chemotherapy. Patients were treated with cisplatin (60 mg m À2 on day 1) and S-1 (orally at 40 mg m À2 per dose, b.i.d., on days 1 -14), with the treatment repeated every 4 weeks for four cycles. Begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
3
31
2
Order By: Relevance
“…Regarding the in vivo experiments, we used S-1 for the 5-FU treatment. Recently, S-1 has been developed for clinical use (16)(17)(18). Many experimental and clinical studies have revealed that the responsiveness to 5-FU is also associated with the intratumoral expression of dihydropyrimidine dehydrogenase (DPD) (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the in vivo experiments, we used S-1 for the 5-FU treatment. Recently, S-1 has been developed for clinical use (16)(17)(18). Many experimental and clinical studies have revealed that the responsiveness to 5-FU is also associated with the intratumoral expression of dihydropyrimidine dehydrogenase (DPD) (8).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the combined treatment with the adenoviral vector expressing shRNA targeting TS and 5-FU has effective antitumor activity against 5-FU-resistant tumor cells in vitro. Finally, the combined treatment with the TS-inhibiting adenoviral vector and an oral 5-FU-derived agent S-1 (a combination of tegafur, gimeracil and oteracil potassium) (16)(17)(18) was found to have effective antitumor activity against 5-FU-resistant tumor xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…The non-inferiority of S-1/CBDCA compared with CBDCA/paclitaxel was confirmed for OS (MST, 15.2 vs. 13.3 months, respectively) (20). As a chemoradiotherapy treatment, two phase II trials of S-1 and CDDP combined with concurrent thoracic radiotherapy were evaluated in patients with locally advanced NSCLC (6,21). The RR, PFS and OS of the trials were 82%, 20 months, and not reached at a follow-up time, and 88%, 12 months and 33.1 months, respectively (6,21).…”
Section: Discussionmentioning
confidence: 99%
“…S-1 was shown to produce an active response as a single agent for metastatic NSCLC with minimal toxicity (2,3). S-1 has been launched for use as a first-line chemotherapy (4) and a second or third-line chemotherapy (5) in advanced stages of the disease, and chemoradiotherapy for stage III (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the first trial conducted by the WJTOG, there was a high response rate of 82% and a median PFS of 20 months; median OS was not reached at a follow-up time range from 24 to 37 months . Another trial of similar schedule and dose that was conducted during almost the same period showed an ORR of 88%, median PFS of 12 months, and a MST of 33.1 months, whereas the median followup time was 25 months, ranging from 12 to 38 months [Ohyanagi et al 2009]. Chemotherapy combined with TRT using systemic doses of S-1 and CDDP has the advantage of eradicating occult distant metastases.…”
Section: Chemoradiotherapy Containing S-1 For Locally Advanced Nsclcmentioning
confidence: 99%